Pelatihan Fisik Berlebih Menurunkan Jumlah Hematopoietic Stem Cells (HSCs) Dibandingkan Pelatihan Fisik Seimbang pada Tikus (Rattus norvegicus) Wistar Jantan - ., Zenitalia; Pangkahila, Alex; Pangkahila, Wimpie; Siswanto, Ferbian M. (Jurnal Biomedik : JBM, 2018)
Abstract: This study was aimed to prove that balanced physical exercise increased mobilization of hematopoietic stem cells (HSCs) compared to excessive physical exercise in male Wistar rats (Rattus norvegicus). This was an experimental study with the randomized pretest-posttest control group design. Subjects were 24 male Wistar rats (Rattus norvegicus), 2.5-3 months old, weighing 180-200 g, healthy (active and did not show any anatomical abnormality), divided into two groups of 12 rats each. One group (P0) was treated with balanced physical exercise and the other group (P1) was treated with excessive physical exercise. Before (pretest) and 4 weeks after treatment (posttest), peripheral blood of 1 ml was drawn through medial canthus sinus orbitalis for examination of HSCs number in peripheral blood quantitatively. The results showed that the number of HSCs in the P0 group was increased from 1.60±0.70 x 106 cell/μl before treatment to 2.70±0.62 x 106 cells/μl after 4-week treatment (P <0.05). Meanwhile, in the P1 group, the number of HSCs was decreased from 1.74±0.68 x 106 cells/μl before treatment to 1.34±0.55 x 106 cells/μl after 4-week treatment (P <0.05). Conclusion: Excessive physical exercise decreased number of hematopoietic stem cells (HSCs) compared to balanced physical exercise in male Wistar rats (Rattus norvegicus).Keywords: balanced physical exercise, excessive physical exercise, hematopoietic stem cells (HSCs)Abstrak: Tujuan penelitian ini ialah untuk membuktikan bahwa pelatihan fisik berlebih menurunkan jumlah hematopoietic stem cells (HSCs) dibandingkan pelatihan fisik seimbang pada tikus (Rattus norvegicus) Wistar jantan. Jenis penelitian ini ialah eksperimental dengan randomized pre-post test control group design. Subyek penelitian ialah 24 ekor tikus Wistar (Rattus norvegicus) jantan, umur 2,5-3 bulan, berat badan 180-200 gr, sehat (aktif dan tidak menunjukkan abnormalitas anatomi) yang dibagi menjadi dua kelompok yaitu P0 dan P1, masing-masing berjumlah 12 ekor. Kelompok P0 diberikan pelatihan seimbang dan kelompok P1 diberi pelatihan fisik berlebih. Sebelum (pretest) dan 4 minggu setelah perlakuan (posttest), darah diambil sebanyak 1 ml melalui medial canthus sinus orbitalis untuk pemeriksaan kadar HSCs darah tepi secara kuantitatif. Hasil penelitian menunjukkan bahwa pada kelompok P0 terjadi peningkatan jumlah HSCs dari 1,60±0,70 x106 sel/μl pretest menjadi 2,70±0,62 x106 sel/μl posttest (P <0,05). Pada kelompok P1 terjadi penurunan jumlah HSCs dari 1,74±0,68 x106 sel/μl pretest menjadi 1,34±0,55 x106 sel/μl posttest (P <0,05). Simpulan: Pelatihan fisik berlebih menurunkan jumlah hematopoietic stem cells (HSCs) dibandingkan pelatihan fisik seimbang pada tikus (Rattus norvegicus) Wistar jantan.Kata kunci: pelatihan fisik seimbang, pelatihan fisik berlebih, hematopoietic stem cells (HSCs)